Quantitative Attribution Analysis of the Spatial Differentiation of Gully Erosion in the Black Soil Region of Northeast China. (20th July 2022) - Wang, Ranghu; Wang, Nan; Fan, Yingchao; Sun, Huan; Fu, Hanpei; Yang, Jiuchun
Abstract : Gully erosion is the major soil erosion type in the black soil region of Northeast China. However, studies on multifactor synthesis at a large scale and on the driving mechanism of spatial differentiation are still relatively lacking for gully erosion in this region. In this study, the simulation of gully erosion and its quantitative attribution analysis have been conducted in the Sancha River catchment in Northeast China, based on high-resolution satellite imagery mapping and the geodetector method. A total of 18 indicators in 6 categories, including topography, climate and weather, soil properties, lithology, land use, have been taken into consideration. The influence of each influencing factor and its interactive influence on gully erosion were quantitatively evaluated. The results showed that at the large catchment scale, the submeter images had a strong capacity for the recognition of a permanent gully and obtained satisfactory results. According to the results of the geodetector, lithology and soil type are the main factors that affect the spatial differentiation of gully erosion in the Sancha River basin, because their interpretation power for gully density and gully intensity was close to 10%. The lithology belonged to gray–white matter rhyolite, spherulite rhyolite, and crystal clastic tuff, with the highest gully density and intensity. The interpretation power of the secondary factors, including rainfall erosivity, watershed area, elevation, soil erodibility, land use pattern, slope, and distance from the river, amounted to more than 1%. The interactions among most driving factors showed nonlinear enhancement. The influence of the interaction between lithology and soil type appeared to be the largest. In particular, the lithology of different soil types accounted for 28.7% and 32.5% of the gully density and gully intensity. The interaction of factors had a stronger influence on the spatial differentiation of gully erosion than any single factor.